1979
DOI: 10.1063/1.326560
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectra from a gas-puff z-pinch device

Abstract: X-ray emission was used to diagnose the plasma formation in a gas-puff pulseddischarge device. X-ray pinhole images were collected simultaneously with x-ray spectra from Ar and Kr gases. X rays were emitted from z-pinched regions (50-100 }-tm in diameter) along a collinear track formed by the plasma implosion of a hollow gas jet. Spectral analysis indicated Ar plasma formation with electron densities of -2 X 10 21 cm -J. The Ar plasma temperature was -1 keV, based on a collisional-radiative transport model. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…As a result, the efficiency of conversion of the energy supplied "from the socket" into the energy of short-wavelength radiation increased. The idea of a multiwire load is close to that of a pulsed gas-puffing load [13,14] or a load created by filling the diode with a laser-produced plasma immediately before the discharge [15,16]. At the same time, the experiments had shown that the results obtained with multiwire and "nonwire" loads of high-current diodes differed dramatically [17,18].…”
mentioning
confidence: 97%
“…As a result, the efficiency of conversion of the energy supplied "from the socket" into the energy of short-wavelength radiation increased. The idea of a multiwire load is close to that of a pulsed gas-puffing load [13,14] or a load created by filling the diode with a laser-produced plasma immediately before the discharge [15,16]. At the same time, the experiments had shown that the results obtained with multiwire and "nonwire" loads of high-current diodes differed dramatically [17,18].…”
mentioning
confidence: 97%
“…X-ray emission is seen pulsing, which is accompanied by local MHD instability. Soft x-ray radiation from hot spots has been observed in the usual z-pinch [5], but x-rays ecceeding 10 keV have not been observed [2]. Since it had been understood that high energy x-rays would be radiated from the device during the process of the experiment, x-ray radiation outside the device was measured for safety.…”
mentioning
confidence: 99%
“…There has been considerable interest in x-ray transitions from high Z atoms with charge states around the neonlike isosequence, attained in pulsed power [1][2][3][4], tokamak [5][6][7][8][9][10] and laser produced [11][12][13] plasmas. X-ray lasing [14,15] has been demonstrated in neonlike ions, and a need to understand the kinetics of this system has motivated development of very precise collisional-radiative modeling tools [16].…”
Section: Introductionmentioning
confidence: 99%